Healthy Lifestyle Promotion for Maintaining Body Mass Index and Enhancing Self-Confidence among Post-Mastectomy Breast Cancer Survivors - Arfah May Syara; Farhah Zaqwa Khairunnisa Damanik; Simson Sinuhaji; Muhammad Reza Fahlevi Hanafi; Yuni Suharnida Lubis; Syatriawati Syatriawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Breast cancer remains one of the most prevalent health problems among women and may cause long-term physical, psychological, social, and emotional consequences. Mastectomy, which is commonly performed as part of breast cancer treatment, can improve survival outcomes; however, postoperative changes in body appearance often affect body image, self-confidence, and the overall quality of life of survivors. In addition, weight fluctuations during the recovery period may influence Body Mass Index (BMI) and psychological well-being. This community service program aimed to improve breast cancer survivors’ knowledge and ability to adopt healthy lifestyle practices for maintaining an optimal BMI, increase awareness of physical and psychological health, and strengthen self-confidence following cancer treatment. The program was implemented using an educational-participatory approach through health education sessions, interactive discussions, nutritional status consultations, light physical activity demonstrations, and experience-sharing sessions. Evaluation was conducted using pretest and posttest assessments involving 20 breast cancer survivors aged 35–60 years at Grandmed Hospital, Lubuk Pakam. The results demonstrated that the proportion of participants with a good level of knowledge increased from 20.0% to 80.0%, while those with poor knowledge decreased from 45.0% to 0%. The mean knowledge score improved from 58.5 to 85.5, representing an increase of 27.0 points (46.2%). Furthermore, 90.0% of participants understood how to maintain an ideal BMI, 100.0% recognized the importance of regular physical activity, and 85.0% reported increased self-confidence after participating in the program. Participant satisfaction ranged from 75.0% to 85.0%. In conclusion, healthy lifestyle promotion was effective in improving knowledge, understanding, and self-confidence among breast cancer survivors, thereby supporting the adoption of sustainable healthy lifestyle behaviors.